Trends and drivers of income inequality in the Philippines, Thailand, and Viet Nam: A decomposition analysis - Rogelio V. Mercado; Cyn-Young Park; Juzhong Zhuang (Asian Development Bank (ADB), 2023)
Over the past 2 decades, income inequality has moderated in three middle-income countries in Southeast Asia-the Philippines, Thailand, and Viet Nam-with multiple factors at play. In each country, wage, nonfarm business income, and overseas remittance concentrations declined as less well-off households increasingly engaged in better-paying activities. In Thailand, private transfers became more pro-poor, and in Viet Nam, public transfers more targeted. Major contributors to lower income inequality also included a narrowing in regional disparity and urban- rural income gaps, and, in the Philippines and Thailand, a fall in the education premium. This recent trend of moderating income inequality might be the combined outcome of rising income opportunities, government policies promoting social inclusion, and positive impacts of structural transformation. Nonetheless, income inequality remains high, especially in the Philippines and Thailand. More policy efforts are still needed to make growth more inclusive.
Keywords: D31; D63; I31; N15; 330; Income inequality; decomposition; Southeast Asia